Diversity patterns of ground-beetles (Coleoptera: Carabidae) along a gradient of land-use disturbance - Silva, Pedro Martins da (2008)
Ground-beetles were used to monitor biodiversity along a gradient of land-use disturbance, from old-growth cork-oak woodland to a monoculture, in a typical Mediterranean landscape. The work also included an exotic forest in the second year. During this study, a total of 11 294 individuals of carabids from 101 different species were sampled (2001: N = 4776, S = 80; 2002: N = 6518, S = 77). Agriculture unit recorded the highest abundance and richness levels, while the exotic forest recorded the lowest values. Moreover, higher diversity levels were observed in units dominated by open areas, particularly pastures. Nevertheless, mosaic units with major cork-oak cover revealed a higher number of species that are more sensitive to human disturbance, i.e., woodland specialists.